Hydrogeochemistry and Isotope Characteristics of the Hot Springs in the Wapsalit Area, Buru Regency, Maluku Province, Indonesia - Pinning, Fathira; Haryanto, Agus Didit; Hutabarat, Johanes (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
Wapsalit is one of the geothermal areas that is located in Buru Regency, Maluku Province. Wapsalit area has several geothermal manifestations like hot springs, altered rocks, silica sinter and many more. This research aims to determine the characteristics and origin of the fluid in the research area. This research takes 5 samples of hot springs named FATH-1, FATH-2, FATH-3, FATH-4 and FATH-5. Based on the results of chemical analysis, it shows that the 5 samples belong to the bicarbonate fluid type. FATH-1, FATH-3 and FATH-5 belong to the partial equilibrium zone, FATH-2 and FATH-4 belong to the immature water zone. Based on isotope 18O and D analysis, the 5 hot spring samples originated from meteoric water and the fluids interacting with the rocks before heading to the surface.